CORRELATION ANALYSIS OF CYTOLOGICAL PARAMETERS AND WOUND HEALING DYNAMICS OF BURN WOUNDS OF RATS USING CHITOSAN MEMBRANES IN THE AGE ASPECT - Kornienko, V.V.; Pogorielov, M.V.; Holubnycha, V.M.; Гусак, Є.В. (World of Medicine and Biology, 2019)
The work is devoted to the study of age-related skin regeneration features using chitosan for the treatment of burns. We simulated IIIb degree burn wounds in rats of the experimental and the control groups. Chitosan films were applied to experimental animals for topical treatment. We have analyzed the burn wounds healing according to cytological criteria, which were measured on the 1st, 3d, 7th, 14th, and the 21st days after modeling the burn. Using the correlation analysis of the interdependency between cytological parameters and the wound healing dynamics, the stimulating effect of chitosan on cells in the burn area was found. Chitosan films improved cleansing of the wound from detritus, prevented cell proliferation and differentiation disorders, reduced the intensity of inflammatory reactions, stimulated the granulation tissue growth, and improved wound epithelization. However, the use of chitosan coatings in 22-month-old rats was less efficient compared to animals of other age groups.